ANALISIS FAKTOR YANG MEMPENGARUHI PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (STUDI EMPIRIS PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2011-2015) - Rio Steven; Vince Ratnawati; Julita Julita (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this research is to analyze the effect caused by company size, profitability, company’s debt level, the intensity of non-current asset ownership, the intensity of inventory ownership, and the tax facility toward the effective tax rate of consumer goods company listed in Indonesia Stock Exchange Year 2011-2015) .The population of this research is all companies engaged in manufacturing sub-sector consumer goods that go public in Indonesia Stock Exchange in 2011-2015 as many as 36 companies. Sample taken by purposive sampling method that determining the sample with certain criteria. Based on the criteria sample, there are only 27 companies that meet the criteria. To analyse data is using multiple linear regression.The research indicates that firm size, company debt level, profitability (ROA) and taxation facility at manufacturing company in Indonesian Stock Exchange in 2011-2015 have a significant effect to the effective tax rate. While the intensity of assets and inventory ownership have no significant effect to the effective tax rate. The magnitude of the effect of firm size, debt level, ROA, asset intensity, inventory intensity and tax facilities to the effective tax rate is 0.168 or 16.8% while 83.20% is influenced by other variables not examined in this study.